Respons Fisiologis Bibit Kopi Robusta dalam Kondisi Cekaman Kekeringan terhadap Aplikasi Trichoderma spp. Cair - Agusty, Reginna Salsabila; Soleh, Mochamad Arief; Zar, Cucu Suherman Victor (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Abiotic stresses caused by climate change can affect on the growth of coffee trees. The application of liquid Trichoderma spp. might stimulate growth and enhance plant defense mechanisms in suboptimal conditions. The purpose of this study was to Evaluating the physiological responses of Robusta coffee seedlings BP 939 and BP 308 and obtaining Robusta coffee seedlings that produce the best physiological responses under drought stress conditions against Trichoderma spp. applications in liquid medium. The experiment was carried out using a Randomized Group Design (RAG) with 8 treatments repeated 4 times, namely : coffea clone BP 939 control; coffea clone BP 308 control.; coffea clone BP 939 Trichoderma spp.; coffea clone BP 308 Trichoderma spp.; coffea clone BP 939 with drought; coffea clone BP 308 with drought; coffea clone BP 939 with drought + Trichoderma spp.; coffea clone BP 308 with drought + Trichoderma spp. The experiment results show that the application of Trichoderma spp. in liquid medium does not exhibit significant physiological responses, and the Robusta coffee seedlings of clones BP 939 and BP 308 show the same effect under drought stress conditions. However, the Robusta coffee clone BP 308 treated with Trichoderma spp. showed significant physiological responses at 12 hours after treatment.